Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(71+65\cdot4=\frac{x+140}{x}+260\)
\(\Rightarrow71+260=\frac{x}{x}+\frac{140}{x}+260\)
\(\Rightarrow71=1+\frac{140}{x}\)
\(\Rightarrow\frac{140}{x}=70\)
\(\Rightarrow x=2\)
71+65*4=x+140 +260
x
=>71+260= x + 140 +260
x x
=>71=1+ 140
x
=> 71-1 = 140
x
=> 70=140:x
=>x=140:70=2
\(71+52,5\times4=\frac{x+140}{x}+210\)
\(71+210=\frac{x+140}{x}+210\)
\(=>\frac{x+140}{x}=71\)
\(71=\frac{142}{2}\)\(\Rightarrow x=142-140=2\)
a) \(\left(2x+1\right)^3=125\)
\(\Rightarrow\left(2x+1\right)^3=5^3\)
\(\Rightarrow2x+1=5\)
\(\Rightarrow2x=5-1\)
\(\Rightarrow2x=4\)
\(\Rightarrow x=4:2\)
\(\Rightarrow x=2\)
Vậy x = 2
b) \(\left(x-5\right)^4=\left(x-5\right)^6\)
\(\Rightarrow\left(x-5\right)^4-\left(x-5\right)^6=0\)
\(\Rightarrow\left(x-5\right)^4\left[1-\left(x-5\right)^2\right]=0\)
\(\Rightarrow\orbr{\begin{cases}\left(x-5\right)^4=0\\1-\left(x-5\right)^2=0\end{cases}}\Rightarrow\orbr{\begin{cases}\left(x-5\right)^4=0\\\left(x-5\right)^2=1\end{cases}}\)
TH 1 : \(\left(x-5\right)^4=0\Rightarrow x-5=0\Rightarrow x=5\)
TH 2 : \(\left(x-5\right)^2=1\Rightarrow\orbr{\begin{cases}x-5=1\\x-5=-1\end{cases}}\Rightarrow\orbr{\begin{cases}x=6\\x=4\end{cases}}\)
Vậy \(x\in\left\{5;6;4\right\}\)
c) \(\left(2x-15\right)^5=\left(2x-15\right)^3\)
\(\Rightarrow\left(2x-15\right)^5-\left(2x-15\right)^3=0\)
\(\Rightarrow\left(2x-15\right)^3\left[\left(2x-15\right)^2-1\right]=0\)
\(\Rightarrow\orbr{\begin{cases}\left(2x-15\right)^3=0\\\left(2x-15\right)^2-1=0\end{cases}}\Rightarrow\orbr{\begin{cases}\left(2x-15\right)^3=0\\\left(2x-15\right)^2=1\end{cases}}\)
TH 1 : \(\left(2x-15\right)^3=0\Rightarrow2x-15=0\Rightarrow2x=15\Rightarrow x=\frac{15}{2}\)
TH 2 : \(\left(2x-15\right)^2=1\Rightarrow\orbr{\begin{cases}2x-15=1\\2x-15=-1\end{cases}}\Rightarrow\orbr{\begin{cases}2x=16\\2x=14\end{cases}}\Rightarrow\orbr{\begin{cases}x=8\\x=7\end{cases}}\)
Vậy \(x\in\left\{\frac{15}{2};8;7\right\}\)
_Chúc bạn học tốt_
\(a,\)\(71+65\times4=\frac{x+140}{x}+260\)
\(\Rightarrow71+260=\frac{x-140}{x}+260\)
\(\Rightarrow71=\frac{x-140}{x}\)
\(\Rightarrow71x=x-140\)
\(\Rightarrow71x-x=-140\)
\(\Rightarrow70x=-140\)
\(\Rightarrow x=-2\)
\(b,\)\(y\times\frac{15}{2}-\frac{1}{3}\times\left(\frac{1}{4}+y\right)=90\frac{2}{3}\)
\(\Rightarrow\frac{15y}{2}-\frac{1}{12}-\frac{y}{3}=\frac{272}{3}\)
\(\Rightarrow\frac{90y}{12}-\frac{1}{12}-\frac{4y}{12}=\frac{1088}{12}\)
\(\Rightarrow90y-1-4y=1088\)
\(\Rightarrow86y=1089\)
\(\Rightarrow y=\frac{1089}{86}\)
a) ( x + 1 ) + ( x + 4 ) + ( x + 7 ) + ( x + 10 ) + ... + ( x + 28 ) = 155
\(\Rightarrow\)( x + x + x + ... + x ) + ( 1 + 4 + 7 + 10 + ... + 28 ) = 155
\(\Rightarrow\)x10 + ( SSH: ( 28 - 1 ) : 3 + 1 = 10 ) = 155
\(\Rightarrow\)x10 + ( Tổng: ( 1 + 28 ) . 10 : 2 = 145 ) = 155
\(\Rightarrow\)x10 + 145 = 155
\(\Rightarrow\)x10 = 155 - 145 = 10
\(\Rightarrow\)x = 10 : 10 = 1
vậy x = 1
b) ( x . 0,25 + 1999 ) . 2000 = ( 53 + 1999 ) .2000
\(\Rightarrow\)500x + 3998000 = 106000 + 3998000
\(\Rightarrow\)500x + 3998000 = 4104000
\(\Rightarrow\)500x = 4104000 - 3998000 = 106000
\(\Rightarrow\)x = 106000 : 500 = 212
X = \(\left(\frac{63}{5\cdot6}-\frac{1}{8}\cdot8+\frac{2}{15}\cdot\frac{3}{100}\right)\cdot\frac{11}{4}\)
X = \(\left(\frac{21}{10}-1+\frac{1}{250}\right)\cdot\frac{11}{4}\)
X = \(\left(\frac{525}{250}-\frac{250}{250}+\frac{1}{250}\right)\cdot\frac{11}{4}\)
X = \(\frac{276}{250}\cdot\frac{11}{4}\)
X = \(\frac{759}{250}\)
\(x+\frac{15}{7}=\frac{9}{2}\)
\(x=\frac{9}{2}-\frac{15}{7}=\frac{33}{14}\)
\(x-\frac{3}{4}=\frac{7}{2}\)
\(x=\frac{7}{2}+\frac{3}{4}=\frac{17}{4}\)
\(x.\frac{7}{8}=\frac{12}{5}\)
\(x=\frac{12}{5}:\frac{7}{8}=\frac{96}{35}\)
\(\frac{5}{6}:x=\frac{4}{3}\)
\(x=\frac{5}{6}:\frac{4}{3}=\frac{5}{8}\)
- a) x=9/2-15/7=33/14
- b) x=7/2+3/4=17/4
- c) x=12/5:7/8=61/35
- d) x=5/6:4/3=5/8
- k nha
\(2009-\left(4\frac{5}{9}+x-7\frac{7}{18}\right):15\frac{2}{3}=2008\)
\(2009-\left(\frac{41}{9}+x-\frac{133}{18}\right):\frac{47}{3}=2008\)
\(\left(\frac{41}{9}+x-\frac{133}{18}\right):\frac{47}{3}=2009-2008\)
\(\left(\frac{41}{9}+x-\frac{133}{18}\right):\frac{47}{3}=1\)
\(\frac{41}{9}+x-\frac{133}{18}=1\cdot\frac{47}{3}\)
\(\frac{41}{9}+x-\frac{133}{18}=\frac{47}{3}\)
\(\frac{41}{9}+x=\frac{133}{18}+\frac{47}{3}\)
\(\frac{41}{9}+x=\frac{415}{18}\)
\(x=\frac{415}{18}-\frac{41}{9}\)
\(x=\frac{37}{2}\)
\(2009-\left(4\frac{5}{9}+x-7\frac{7}{18}\right)\div15\frac{2}{3}=2008\)
\(\left(4\frac{5}{9}+x-7\frac{7}{18}\right)\div15\frac{2}{3}=2009-2008\)
\(\left(-3\frac{3}{18}+x\right)\div15\frac{2}{3}=1\)
\(-3\frac{3}{18}+x=15\frac{2}{3}\)
\(x=15\frac{2}{3}+3\frac{3}{18}\)
\(x=15\frac{12}{18}+3\frac{3}{18}\)
\(x=18\frac{15}{18}\)
exactly 100%
b) 140:(5*x-15)=4
=> 5*x-15=140:4
=> 5*x-15=35
=> 5*x =35+15
=> 5*x =50
=> x =50:5
=> x=10
x=10